DEMOGRAPHICS OF TUBERCULOSIS IN DISTRICT MANSEHRA - Kamal, Muhammad; Ali, Shafqut; Hussain, Syed Javed; Abbasi, Munir Ahmad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Tuberculosis is one of the leading causes of morbidity and mortality across the globe. Pakistan is one of the 22 high tuberculosis burden countries of the world sharing more than 80% of the global burden of tuberculosis. Methods: This study was a retrospective case-based study that analyzed secondary data obtained from TB-03 form at the office of the District Tuberculosis Control Officer (DTO), Mansehra. Data was entered into SPSS-20 and analyzed. Results: A total of 625 patients with a mean age of 32.1±19.1 years were registered at the DTO office during the year 2013. Most of the patients were female (57%) as compared to males (43%). The most common treatment outcome was treatment completed, recorded against 56% of the patients. The proportion of patients declared cured at the end of the treatment was 236 (37.8%). There were only 4 (0.64%) cases of treatment failure during 2013. Conclusion: Despite falling incidence of tuberculosis and mortality across the globe, tuberculosis is still a major determinant of disease in our society. Aggressive case detection and treatment is needed to manage this disease.